The transformation from traditional markets to digital markets - BENAMMAR, Sihem; BENDAOUDIA, Ahmed; KOUADRI BOUDJELTHIA, Amina (The International tax journal, 2025)
This article examines how rapid technological advances have profoundly transformed behaviour and business models. Digital models have supplanted traditional market structures, relying on technology and data as the primary sources of value and competitive advantage. Meta illustrates this transformation: thanks to platform-based, data-driven business models, the company has become a dominant global digital player. While this transformation promotes efficiency, personalisation and strategic decision-making, it also raises significant challenges related to market monopolies, transparency and user rights, highlighting the need for updated regulatory frameworks.